Comment on “Examining Tang and Song Yingtang image halls from a clan sacrificial perspective” - Zhao, Yang (2023)
Reference to the commented article: CHENG, Wanli. Examining Tang and Song Yingtang image halls from a clan sacrificial perspective. Trans/Form/Ação: Unesp Journal of Philosophy, v. 46, n. 3, p. 229 - 248, 2023.